Стратегічні прорахунки маркетингу освітніх послуг на сучасному етапі розвитку України - Яковенко, Р. В.; Yakovenko, R. (Ексклюзив-систем, 2017)
Проаналізовано наслідки залежності фінансування освіти від кількості студентів та відповідної маркетингової стратегії вищих навчальних закладів щодо залучення студентів. The consequences of the dependence of education financing on the number of students and the corresponding marketing strategy of higher educational institutions on attracting students are analyzed.
Strategic miscalculations of marketing of educational services at the present stage of Ukraine’s development
Keywords: демографічна криза; фінансування освіти; розвиток людини; якість навчання; demographic crisis; financing of education; human development; quality of education